Fluoroscopy-guided balloon dilation of a proximal urethral stricture caused by a urethral membrane in a female cat. Issue 2 (August 2019) - Rincon Alvarez, Javier; Smith, Victoria; Broome, Cameron
Case summary: A proximal urethral stricture was diagnosed by retrograde urethrogram in a 2-year-old female neutered cat, which was referred following a 2-month history of stranguria, pollakiuria and urinary incontinence. Cystoscopic examination confirmed the presence of a severe narrowing of the proximal urethra near to the bladder neck, consisting of a membrane arising from the urethral mucosa. Fluoroscopy-guided balloon dilation was performed. Twelve months after the procedure, the cat did not show any recurrence of clinical signs. Relevance and novel information: To our knowledge, this is the first report of a proximal urethral stricture in a cat. Management by fluoroscopy-guided balloon dilation proved to be a successful and minimally invasive option with an excellent outcome.